TEACHING VOCABULARY RELATED TO SEISMIC SAFETY FOR CADETS-RESCUERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores effective methods of teaching vocabulary related to seismic safety for cadets-rescuers. It emphasizes the significance of specialized terminology in the professional development of future rescuers and outlines pedagogical approaches that enhance lexical competence. Special focus is given to practical exercises, simulation tasks, and bilingual glossaries that allow cadets to master seismic safety vocabulary in real-life contexts.